Tamarindo (Tamarindus indica L.) desidratado: efeito de redução da acidez e do teor de sólidos da polpa no processo de liofilização, na composição de metabólitos e estabilidade na estocagem - Maia, Monique de Oliveira (2019)
The tamarind pulp (Tamarindus indica L.) contain fibers and phenolic compounds which makes it attractive for the elaboration of products with economical and nutritional potential. However, the characteristic acid taste is a sensory barrier and may cause problems in the dehydration of the pulp by lyophilization. This thesis’ objective was the evaluation of acidity reduction and solids content in tamarind pulp submitted to lyophilization process, its effects on chemical composition and stability. The drying condition was evaluated by reduction of acidity (Control and Neutralized treatments, respectively, C = pH 3.5 and N = pH 2.5) and by the variation of the solids content, ST (30, 25, 20, 15 and 10%) of the pulp and adjustment of the parameters of time and temperature in the process. The in natura and the hydrated pulp, and also the powder were characterized as for the physicochemical and centesimal composition. The tamarind pulp C and N with different ST contents were evaluated for melting point by Differential Scanning Calorimetry (DSC). The melting data of the pulps supported two heating program settings (A and B). The effect of the reduction of acidity was evaluated in chemical composition by Nuclear Magnetic Resonance (NMR) and Ultra Performance Liquid Chromatography (UPLC-ESI-Q-TOF-MSE). The tamarind pulp powder stability (C and N) with and without anti-caking (CaCO3 2.5%) was evaluated for microbiological parameters, physical and flow properties. As well as moisture of equilibrium by sorption isotherms. The results indicated that the acidity reduction had a positive effect on the freeze drying of the tamarind pulp and did not significantly influence (p> 0.05) in the composition of the chemical compounds quantified by NMR. The adjustment of the heating program with less time to primary drying using the 20% solids content minimizes the occurrence of collapse of the C and N pulp. The Compound putatively detected in UPLC-ESI-Q-TOF-MSE indicated the presence of phenolic compounds, mainly represented by phenolic acids, catechin and cyanidin. In the study of the tamarind pulp powder the GAB model was evidenced as more appropriate to describe the adsorption isotherms of the tamarind pulp powder of all treatments. In relation to stability, all treatments (C and N) with and without CaCO3 shown difficulty in the flow and a high degree of caking, especially the treatments C and C + CaCO3. However, in the other parameters evaluated were satisfactory and indicate the stability of the tamarind pulp powder during 150 days of storage for all treatments. This factor was allied to the condition provided by the packaging. The nylon / aluminum / polyethylene layers acted as a barrier preventing microbial contamination, moisture inflow and kept levels of hygroscopicity and solubility stable. These aspects were critical in the conservation and stability of the product in 150 days at room temperature.